The inguinal macroglands of the frog Physalaemus nattereri (Leptodactylidae): structure, toxic secretion and relationship with deimatic behaviour - Lenzi-Mattos, R.; Antoniazzi, M. M.; Haddad, CFB; Tambourgi, D. V.; Rodrigues, M. T.; Jared, C. (Cambridge University Press, 2005)
Amphibian skin is characterized by the presence of mucous glands, related to cutaneous breathing, reproduction and water balance, and granular glands, related to the production of toxins used in defence. In some species the granular glands can form accumulations in certain regions of the body. This is the case for inguinal macroglands of the leptodactylid frog Physalaemus nattereri, where these structures form a pair of black discs associated with deimatic behaviour. The morphology of the inguinal macroglands and their secretion were studied in this species and correlated to deimatic behaviour. The inguinal macroglands are formed from elongated granular glands that, in contrast with the granular glands of the rest of the skin, have small spherical granules with a proteinic content. In the dermis of the whole body, except for the inguinal macroglands and the inguinal region, a well-developed calcified dermal layer is observed. During deimatic behaviour these macroglands discourage a potential predator from attacking, but if visual cues are insufficient and the predator persists in the attack, atoxic secretion is eliminated in its mouth. This elimination is favoured by the absence of a calcified dermal layer in the macroglands, which makes the dermal region softer than the rest of the dorsal skin.
Keywords: Amphibia; integument; inguinal macroglands; skin secretion; Phlysalaemus nattereri; defence